Culture, Communication and Hybridity: The Case of The Rap of China. Issue 2 (3rd April 2019) - Flew, Terry; Ryan, Mark; Su, Chunmeizi
ABSTRACT: This paper proposes that cultural hybridity presents an important way of synthesizing the study of culture and communication in the context of globalization. It explores the historical development of rap and hip-hop as translocal cultural forms, that have their roots in U.S. African-American culture, but have been adapted in multiple 'translocal' contexts around the world. It takes the highly successful Chinese online entertainment program The Rap of China as a case study in how such a 'foreign' cultural form is adapted and modified in a distinctive political, cultural and media context, and how streaming services such as iQIYI are carrying new and innovative cultural product. It also notes tensions that surround rap and hip-hop in China, particularly around forms of cultural expression, the aspirations of young Chinese, the desire to reach international markets with Chinese television product, and the ambivalent stance of the agencies of the Chinese party-state towards it.